Studi Kitab Syarh Shahih al-Bukhari Karya Ibnu Bathal - Kinkin Syamsudin (Universitas Islam Negeri Imam Bonjol Padang, 2021)
Sahih al-Bukhari is a phenomenal book among the many books of hadith that have been written, and one form of attention of the scholars to it is to make a book of syarah. The existing syarah books were written by scholars from various schools of thought, one of which was written by Ibnu Battal who is affiliated to the Maliki school of thought. Using library research and content analysis, this article was written to find out the methodology for writing Ibnu Bathal's Syarah Sahih al-Bukhari above and to reveal its differences with other books of Syarah Sahih al-Bukhari. From this research, it can be seen that the peculiarities of Ibn Battal's work are; first, he did not discuss the narrators and sanad specifically, but directly mentioned the name of the companions who was the narrator of the hadith. Second, he explained the matan of the hadith without discussing ikhtilaf or the differences in the editorial differences of the matan first. Third, in understanding the difference in understanding of the matter in dispute, especially with regard to law, he prefers to take interpretations from the Maliki school of thought